2D Hexagonal Boron Nitride (2D‐hBN) Explored as a Potential Electrocatalyst for the Oxygen Reduction Reaction. Issue 2 (28th September 2016) - Khan, Aamar F.; Randviir, Edward P.; Brownson, Dale A. C.; Ji, Xiaobo; Smith, Graham C.; Banks, Craig E.
Abstract: Crystalline 2D hexagonal Boron Nitride (2D‐hBN) is explored as a potential electrocatalyst towards the oxygen reduction reaction (ORR) when electrically wired via a drop‐casting approach upon a range of carbon based electrode surfaces; namely, glassy carbon (GC), boron‐doped diamond (BDD), and screen‐printed graphitic electrodes (SPEs). We consider the ORR in acidic conditions and critically evaluate the performance of unmodified and 2D‐hBN modified electrodes, implementing coverage studies (commonly neglected in the literature) in order to ascertain the true impact of this novel nanomaterial. The behaviour of 2D‐hBN towards the ORR is shown to be highly dependent upon both the underlying carbon substrate and the coverage/mass utilised. 2D‐hBN modified SPEs are found to exhibit the most beneficial response towards the ORR, reducing the peak potential by ca . 0.28 V when compared to an unmodified/bare SPE. Such improvements at this supporting substrate are inferred due to favourable 2D‐hBN interaction with ridged surfaces exposing a high proportion of edge regions/sites, where conversely, we show that relatively smooth substrate surfaces (such as GC) are less conducive towards successful 2D‐hBN immobilisation. In this paper, we reveal for the first time (in the specific case of using a rough supporting substrate) that 2D‐hBN gives rise to beneficial electrochemical behaviour towards the ORR. Unfortunately, this material is not considered an electrocatalyst for use within fuel cells given that the estimated number of electrons transferred during the ORR ranges between 1.90–2.45 for different coverages, indicating that the ORR at 2D‐hBN predominantly produces hydrogen peroxide. 2D‐hBN does however have potential and should be explored further by those designing, fabricating and consequently electrochemically testing modified electrocatalysts towards the ORR. Abstract :